KAJIAN PEMBANGUNAN PARIWISATA PANTAI SUWUK KABUPATEN KEBUMEN DITINJAU DARI ASPEK PARTISIPASI MASYARAKAT (STUDI PADA MASYARAKAT DUKUH SUWUK DESA TAMBAKMULYA) (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2014)
Tourism development requires community participation as a condition for the success of tourism development. This study discusses community participation in tourism development of Suwuk Beach of Kebumen Regency using quantitative methods to measure the seven indicators of participation that is planning and implementing tourism strategies, achievement of sustainable tourism development, improvement tourist satisfaction, better tourism planning, fair distribution of costs and benefits involving stakeholders, compliance of the locals needs, and strengthening the process of democratization at tourist destination. The result showed the community in Suwuk Beach classified as participatory community in tourism development of Suwuk Beach in Kebumen Regency.